Short- versus long-course antibiotic therapy for sepsis: a post hoc analysis of the nationwide cohort study - Nozomi Takahashi; Taro Imaeda; Taka‑aki Nakada; Takehiko Oami; Toshikazu Abe; Yasuo Yamao; Satoshi Nakagawa; Hiroshi Ogura; Nobuaki Shime; Asako Matsushima; Kiyohide Fushimi (Journal of Intensive Care, 2022)
Abstract Background The appropriate duration of antibiotic treatment in patients with bacterial sepsis remains unclear. The purpose of this study was to evaluate the association of a shorter course of antibiotics on 28-day mortality in comparison with a longer course using a national database in Japan. Methods We conducted a post hoc analysis from the retrospective observational study of patients with sepsis using a Japanese claims database from 2010 to 2017. The patient dataset was divided into short-course (≤ 7 days) and long-course (≥ 8 days) groups according to the duration of initial antibiotic administration. Subsequently, propensity score matching was performed to adjust the baseline imbalance between the two groups. The primary outcome was 28-day mortality. The secondary outcomes were re-initiated antibiotics at 3 and 7 days, during hospitalization, administration period, antibiotic-free days, and medical cost. Results After propensity score matching, 448,146 pairs were analyzed. The 28-day mortality was significantly lower in the short-course group (hazard ratio, 0.94; 95% CI, 0.92–0.95; P < 0.001), while the occurrence of re-initiated antibiotics at 3 and 7 days and during hospitalization were significantly higher in the short-course group (P < 0.001). Antibiotic-free days (median [IQR]) were significantly shorter in the long-course group (21 days [17 days, 23 days] vs. 17 days [14 days, 19 days], P < 0.001), and short-course administration contributed to a decrease in medical costs (coefficient $-212, 95% CI; − 223 to − 201, P < 0.001). Subgroup analyses showed a significant decrease in the 28-day mortality of the patients in the short-course group in patients of male sex (hazard ratio: 0.91, 95% CI; 0.89–0.93), community-onset sepsis (hazard ratio; 0.95, 95% CI; 0.93–0.98), abdominal infection (hazard ratio; 0.92, 95% CI; 0.88–0.97) and heart infection (hazard ratio; 0.74, 95% CI; 0.61–0.90), while a significant increase was observed in patients with non-community-onset sepsis (hazard ratio; 1.09, 95% CI; 1.06–1.12). Conclusions The 28-day mortality was significantly lower in the short-course group, even though there was a higher rate of re-initiated antibiotics in the short course.